AGREE-S: AGREE II extension for surgical interventions: appraisal instrument - Antoniou, SA; Florez, ID; Markar, S; Logullo, P; López-Cano, M; Silecchia, G; Antoniou, GA; Tsokani, S; Mavridis, D; Brouwers, M; Dayem, YSA; Bertolaccini, L; et al. (Springer, 2022)
Background: The Appraisal of Guidelines Research and Evaluation (AGREE) II instrument was developed to evaluate the quality of clinical practice guidelines. Evidence suggests that development, reporting, and appraisal of guidelines on surgical interventions may be better informed by modification of the instrument.